Respuesta :

qabtt

Let's first see if we can solve this quadratic equation by factoring.


After listing the factors of -36, are there any that will add to 9? After some guessing and checking, you can realize that 12 and -3 will multiply to -36 and add to 9.


Thus, we can simplify our quadratic equation as follows:

[tex]x^2 + 9x - 36 = 0[/tex]

  • Set up

[tex](x + 12)(x - 3) = 0[/tex]

  • Factor

[tex]x + 12 = 0 \,\,\,\, \textrm{and} \,\,\,\,x - 3 = 0[/tex]

  • Apply the Zero Product Property

[tex]x = 3, -12[/tex]

  • Solve both equations